The Convergence of Organizational Culture, Structure and Human Capital Performance: A Conceptual Analysis - Peprah, Williams Kwasi; Ganu, Josephine (Archives of Business Research, 2018)
There is no doubt that talented employees are the backbone of every organizational success. An organization can have an advantage over its competitors by using better technology, lower costs, more innovative products, etc. However, these advantages do not just happen by themselves; it takes talents within the organization to create, implement and sustain competitive advantages. Thus, the long-term success of any organization ultimately depends on maximizing the effectiveness of employees in accomplishing organizational goals. The key to the desired results is creating a favourable context within which employees must operate. Hence, organizational structure and culture are key to employees’ effectiveness. Therefore, using literature review method, this conceptual paper examined the roles of organizational culture and organizational structure in maximizing human capital performance. Further, this article recommends research propositions based on a framework for an empirical examination of the relationships and impact of organizational culture and structure on human capital performance and sustainable competitive advantage.